2023
DOI: 10.3390/molecules28124626
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Properties of Vegetable Films Based on Pumpkin Purée and Biopolymers of Plant and Animal Origin

Abstract: Highly methylated apple pectin (HMAP) and pork gelatin (PGEL) have been proposed as gelling agents for pumpkin purée-based films. Therefore, this research aimed to develop and evaluate the physiochemical properties of composite vegetable films. Granulometric analysis of film-forming solutions showed a bimodal particle size distribution, with two peaks near 25 µm and close to 100 µm in the volume distribution. The diameter D4.3, which is very sensitive to the presence of large particles, was only about 80 µm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the activation time directly affects the efficiency of covalent immobilization of beta-galactosidase from Aspergillus oryzae on multi-walled amino-functionalized carbon nanotubes. For instance, a study has demonstrated that the activation time significantly improves the efficiency of immobilization when prolonged [ 50 ]. In discussing the outcomes related to each significant factor's individual effects, it's apparent that this factor has the potential to enhance the influence of other crucial factors, such as the combined effect of pH activation + activation time, buffer pH + activation pH, activation pH + buffer molarity, and glutaraldehyde molarity + MWCNT-NH2-glutaraldehyde .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the activation time directly affects the efficiency of covalent immobilization of beta-galactosidase from Aspergillus oryzae on multi-walled amino-functionalized carbon nanotubes. For instance, a study has demonstrated that the activation time significantly improves the efficiency of immobilization when prolonged [ 50 ]. In discussing the outcomes related to each significant factor's individual effects, it's apparent that this factor has the potential to enhance the influence of other crucial factors, such as the combined effect of pH activation + activation time, buffer pH + activation pH, activation pH + buffer molarity, and glutaraldehyde molarity + MWCNT-NH2-glutaraldehyde .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, most research is still at the laboratory stage, especially regarding by-products from processing. It can be noted that some fruits contain enough pectins to make it possible to produce continuous materials without the addition of gelling agents, such as apple, black currant, or plum [34]. However, vegetables are characterized by different compositions, and the beetroot pomace produced during juice processing that was used in this study did not contain a sufficient amount of gelling compounds to create thin layers of vegetable snacks (Figure 1).…”
Section: Vegetable Crispbread Characterization and Microstructurementioning
confidence: 97%